2022
DOI: 10.1021/acs.est.1c05812
|View full text |Cite
|
Sign up to set email alerts
|

Photoaging of Baby Bottle-Derived Polyethersulfone and Polyphenylsulfone Microplastics and the Resulting Bisphenol S Release

Abstract: This study evaluated the release of bisphenol S (BPS) from polyethersulfone (PES) and polyphenylsulfone microplastics (MPs) derived from baby bottles under UV irradiation. Released BPS fluctuates over time because it undergoes photolysis under UV254 irradiation. Under UV365 irradiation, the highest released concentration at 50 °C was 1.7 and 3.2 times that at 35 and 25 °C, respectively, as the activation energy of the photochemical reactions responsible for MP decay was reduced at high temperatures. Low concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(9 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Besides undergoing degradation, MNPs also release toxic chemicals and interact with other pollutants within organisms. The release of toxic chemical additives such as N -(1,3-dimethylbutyl)- N ′-phenyl- p -phenylenediamine, heavy metals, phthalate, and bisphenol by MNPs into natural environments is well established. A recent study demonstrated that PLA MPs release oligomer NPs during the gastrointestinal processes in mice but could not elucidate the mechanisms . Toxic additives may also be released from MNPs due to the complex environmental conditions in the human body, including acids, enzymes, and gut microflora; however, current information is limited.…”
Section: Fates Of Mnps In the Human Bodymentioning
confidence: 99%
“…Besides undergoing degradation, MNPs also release toxic chemicals and interact with other pollutants within organisms. The release of toxic chemical additives such as N -(1,3-dimethylbutyl)- N ′-phenyl- p -phenylenediamine, heavy metals, phthalate, and bisphenol by MNPs into natural environments is well established. A recent study demonstrated that PLA MPs release oligomer NPs during the gastrointestinal processes in mice but could not elucidate the mechanisms . Toxic additives may also be released from MNPs due to the complex environmental conditions in the human body, including acids, enzymes, and gut microflora; however, current information is limited.…”
Section: Fates Of Mnps In the Human Bodymentioning
confidence: 99%
“…The latest study found the presence of MPs in the blood of living people for the first time, indicating that MPs are bioavailable and can be transferred to human blood and various organs of the human body . Meanwhile, some studies have found that a large number of S-MPs are present in baby bottles, as well as in human feces and sputum . Therefore, understanding the S-MPs after photoaging helps in assessing the potential environmental risks of MPs.…”
Section: Environment Implicationsmentioning
confidence: 99%
“…67 Meanwhile, some studies have found that a large number of S-MPs are present in baby bottles, as well as in human feces and sputum. 68 Therefore, understanding the S-MPs after photoaging helps in assessing the potential environmental risks of MPs. In this study, we found that S-MPs under simulated light irradiation generated sulfur-centered radicals and thio−oxygen radicals.…”
Section: ■ Environment Implicationsmentioning
confidence: 99%
“…[7][8][9] The use of such synthetic dyes makes the world colorful, but their discharge into the aquatic environment endangers aquatic and human lives. Malachite green, 10 methylene blue (MB), 11 phenols, 12 and pesticides 13,14 are some examples of the colored toxicants that not only deteriorate the quality of water but also increase the levels of chemical oxygen demand (COD) and biological oxygen demand (BOD). Numerous colored toxins have mutagenic effects, posing significant risks to human health by inducing renal failure and causing damage to the reproductive and central nervous systems.…”
Section: Introductionmentioning
confidence: 99%